2021
DOI: 10.1177/0034355220980808
|View full text |Cite
|
Sign up to set email alerts
|

Technology and Communication Considerations for Engaging Youth Receiving Supplemental Security Income (SSI) Benefits: Vocational Rehabilitation Counselor Perspectives

Abstract: Technology has been shown to enhance daily activities, increase participation in individualized planning and supports, and accommodate the transition needs of students with disabilities. This study examined the benefits and challenges regarding technology use when providing transition services for youth and families receiving Supplemental Security Income (SSI) benefits. Specifically, it explored the nuances of employing technology to encourage engagement in Wisconsin Promoting the Readiness of Minors in Supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Previous research and the findings of this study demonstrate comprehensive, employment-focused case management for youth with disabilities that combines VR and WIOA Title I and III services to ensure early engagement in paid work experiences and individualized career development, including career pathways and apprenticeship options, significantly increases the likelihood that youth with disabilities will obtain CIE and have higher quarterly earn-ings (Anderson et al, 2021;Cocks et al, 2015;Hartman et al, 2021;Mazzotti et al, 2021;Wehman et al, 2017). Therefore, it is recommended that VR seek to increase the number of applications for VR services from students with disabilities receiving Pre-Employment Transition Services to ensure access to individualized career planning and development.…”
Section: Recommendationsmentioning
confidence: 75%
See 2 more Smart Citations
“…Previous research and the findings of this study demonstrate comprehensive, employment-focused case management for youth with disabilities that combines VR and WIOA Title I and III services to ensure early engagement in paid work experiences and individualized career development, including career pathways and apprenticeship options, significantly increases the likelihood that youth with disabilities will obtain CIE and have higher quarterly earn-ings (Anderson et al, 2021;Cocks et al, 2015;Hartman et al, 2021;Mazzotti et al, 2021;Wehman et al, 2017). Therefore, it is recommended that VR seek to increase the number of applications for VR services from students with disabilities receiving Pre-Employment Transition Services to ensure access to individualized career planning and development.…”
Section: Recommendationsmentioning
confidence: 75%
“…PROMISE youth case management and family supports aided youth with disabilities and their families in navigating systems to increase engagement in paid work experiences, career development, and employment. The Wisconsin PROMISE model demonstrated that intentionally connecting youth receiving SSI benefits with the public VR program using targeted outreach strategies resulted in increased employment for these youth (Anderson et al, 2021;Hartman et al, 2021). Furthermore, an external longitudinal evaluation of the Wisconsin PROMISE model confirmed the importance of early employment experiences with wraparound supports have a positive impact on youth employment five years following the initial receipt of services (Patnaik et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Barriers to support noted by our participants included skill with technology-of interest given present COVID-19 restrictions placing greater emphasis on virtual platforms now and in the future. 20 Online service connections, software applications, and devices themselves may pose a barrier to care partners of any age 21,22 ; technology applications in health will continue to reveal access inequities across populations. 23 Additionally, our sample included those who traveled great distances for care.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clients believed ICT was acceptable because “counselors responded more quickly to email responses than phone messages, it was a quick way to communicate between in-person meetings,” and it provided “documentation they could refer back to for clarification” ( Ipsen et al, 2012 , p. 177). Today, new generations of transition-age youth with disabilities increasingly prefer text communication with rehabilitation counselors ( Anderson et al, 2021 ). Yet, it was not until the highly contagious COVID-19 virus that rehabilitation counselors were forced, for the first time, to interact with their clients exclusively via ICT applications.…”
mentioning
confidence: 99%